Sosialisasi Penggunaan Teknologi Digital dalam Memasarkan UMKM di Desa Simaninggir Kecamatan Sitahuis Kabupaten Tapanuli Tengah - Donny Salsabila Daulay; Adinda Elisabet (Universitas 45 Surabaya, 2024)
Socialization of the use of digital technology in marketing MSMEs aims to help MSME actors increase competitiveness and expand market reach. Through this socialization, the community is taught about understanding digital technology in facing the era of globalization and inspiring MSME actors to be more innovative in creating products and marketing strategies. After Simaninggir Village participated in the socialization of the use of digital technology, it is hoped that the community will be able to increase online marketing through social media such as Facebook, Instagram, WhatsApp, and TikTok which are often used every day.